DIFFERENCES OF CORAL REEF AND CORAL COMMUNITY FISH ABUNDANCE CONDITION BASED ON ZONING OF BENGKOANG ISLAND, KARIMUNJAWA - M. Nadia; N Nurhidayah; H. Alkharis; Muhammad Danie Al Malik (Jurnal Kelautan, 2018)
Bengkoang Island is an unpopulated island in the northern region of the archipelago. The island is divided into 2 zones, Marine Protection Zone and Marine Tourism Utilization Zone, based on the zoning and management plan of the Karimunjawa National Park, Central Java. This research is aimed to observe the condition of the coral reef and coral community fish abundance in Bengkoang Island based on the zoning. There were 2 stations to represent each of the zones at depths of 5 and 10 meters. Line Intercept Transect (LIT) method was used along 100 meters to data the reef substrate and Visual Census method with Belt Transect was used to data the coral community fish. The result showed that the coral cover was the highest in Station 1 at 5 m which was located in the Marine Protection Zone with 80,31%, while the lowest was found in Station 2 at 10 m which was located in the Marine Tourism Utilization Zone with 18,81%. Meanwhile, the coral community fish abudance was the highest in Station 1 at 10 m with 15.600 individual/ha and lowest in Station 2 at 10 m with 4.280 individual/ha. Based on the result, it can be said that the condition of the coral reef ecosystem in Bengkoang Island varies with a high margin between the data stations. The result indicated that the coral reef ecosystem in the Marine Protection Zone was in a better condition than in the Marine Toursim Utilization Zone.DIFFERENCES OF CORAL REEF AND CORAL COMMUNITY FISH ABUNDANCE CONDITION BASED ON ZONING OF BENGKOANG ISLAND, KARIMUNJAWAABSTRACTBengkoang Island is an unpopulated island in the northern region of the archipelago. The island is divided into 2 zones, Marine Protection Zone and Marine Tourism Utilization Zone, based on the zoning and management plan of the Karimunjawa National Park, Central Java. This research is aimed to observe the condition of the coral reef and coral community fish abundance in Bengkoang Island based on the zoning. There were 2 stations to represent each of the zones at depths of 5 and 10 meters. Line Intercept Transect (LIT) method was used along 100 meters to data the reef substrate and Visual Census method with Belt Transect was used to data the coral community fish. The result showed that the coral cover was the highest in Station 1 at 5 m which was located in the Marine Protection Zone with 80,31%, while the lowest was found in Station 2 at 10 m which was located in the Marine Tourism Utilization Zone with 18,81%. Meanwhile, the coral community fish abudance was the highest in Station 1 at 10 m with 15.600 individual/ha and lowest in Station 2 at 10 m with 4.280 individual/ha. Based on the result, it can be said that the condition of the coral reef ecosystem in Bengkoang Island varies with a high margin between the data stations. The result indicated that the coral reef ecosystem in the Marine Protection Zone was in a better condition than in the Marine Toursim Utilization Zone. Key Words: Karimunjawa, Bengkoang Island, Zoning, Coral Reef, Coral Fish